Quadruple in Development Sharia Economics in Indonesia - Sulvia Triana Hapsari; Abdul Madjid; Nurini Aprilianda (Faculty of Law, Universitas Jenderal Soedirman, 2022)
Quadruple helix is a quality of legal audit system in various aspects that provides effectiveness and efficiency in the application of law in society. Business (tijarah) is one of the main components in the Islamic economics. Therefore, Islam recommends its adherents to engage in this field professionally (itqan), so that they can benefit themselves, their families and Muslims in general. The formulation of the problem is what is the role of the quadruple helix in Islamic economics in Indonesia? The research method used is normative juridical. This type of legal research is carried out by examining secondary data in the field of law as library data using deductive thinking methods. The approach used in addressing the problem is to use the statutory approach (statue approach). The conclusion is that with the quadruple helix the application of regulations related to Islamic economics can achieve legal goals in Indonesia.Keywords: sharia economics; quality of legal audit; effectiveness and efficiency.